ANALISIS MANAJEMEN BISNIS SYARIAH PRODUKSI PETANI KOPI (STUDI PETANI KOPI GUNUNG GAGAK DESA PURWABAKTI, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR, JAWA BARAT) - Hanifah, Ilham Mohammad; Thantawi, Tubagus Rifqy; Melinasari, Susi (Sahid Business Journal : Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2024)
This research was motivated by the high potential development of coffee plant production in Bogor district, especially the Pamijahan sub-district. And this study aims to determine the production management pattern applied by Gunung Gagak coffee farmers in Purwabakti Village, Pamijahan District, Bogor Regency. This research is qualitative and data collection method by conducting interviews, observation and documentation. This data collection method was carried out on respondents, namely coffee farmers, local government and community leaders. Observations and documentation were carried out in the cultivation area of Gunung Gagak coffee plants, Purwabakti village, Pamijahan district. The analysis used in this study was qualitative descriptive. The results showed that the production management pattern applied by the farmers of Gunung Gagak coffee cultivation was in accordance with the Sharia Business Management perspective. Farmers have carried out their duties quite well in accordance with Sharia Business Management in terms of producing, marketing, maintaining, utilizing, and preserving the natural wealth created by Allah SWT.